Efektifitas Penerapan Terapi Afirmasi Positif untuk Menurunkan Tanda dan Gejala Harga Diri Rendah Pada Pasien Skizofrenia di Panti Gramesia Cirebon - Putri Nurfitriani; Meyra Nur Rizkyllah2 (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Schizophrenia is a severe mental disorder that affects multiple psychological functions, including cognitive processes, communication abilities, and emotional expression. According to the World Health Organization (WHO) in 2019, approximately 20 million people worldwide were living with schizophrenia. One of the common problems experienced by individuals with schizophrenia is low self-esteem. This study aimed to evaluate the effectiveness of Positive Affirmation Therapy in reducing symptoms of low self-esteem among patients at Panti Gramesia Cirebon. The method employed was a nursing care report structured according to the stages of the nursing process, including assessment, diagnosis, planning, implementation, and evaluation. The intervention was conducted in three sessions, each lasting one hour. Observational findings indicated an improvement in the patient’s condition following the intervention. Initially, the score of low self-esteem signs and symptoms was 29. After the implementation of therapy, the score gradually decreased to 22. These findings suggest that the combination of pharmacotherapy and Positive Affirmation Therapy contributed to the reduction of low self-esteem manifestations. In conclusion, Positive Affirmation Therapy shows potential effectiveness in decreasing symptoms of low self-esteem and supporting improvements in patients’ quality of life.